Chapter Da convitato di pietra a protagonista: appunti per una storia del tirocinio - Oliviero, Stefano (Strumenti per la didattica e la ricerca, 2022)
Practical traineeship has reached a stage of high juridical and scientific recognition in the initial training courses to become preschool and primary school teachers, but also in the field of methodological and didactic studies. Indeed, since its introduction in the university pathway, at the same time as the birth of degree courses in Science of Primary Education in the nineties of the twentieth century and in the wake of what is provided by the Delegated Decrees, practical traineeship activities have reached a very mature degree of definition. To talk about direct digital integrated practical traineeship (TDDI) means to insert the discourse in the evolutionary line just mentioned. However, in this contribution I will focus only on some steps that I think are useful to reflect on the TDDI experience.